Biosynthesis of Silver Nanoparticles from Kepundung Fruit Peel (Baccauera Racemose) and Their Application in Mercury Detection Using Digital Image Colorimetric Methods - Irhas Anugrahadi Habibie; Apriliya Ningsih; Yogi Dian Kusuma; Riska Sukma Wardani; Dhity Rismawati; Murniati Murniati (Jurnal Kimia Sains dan Aplikasi, 2024)
Mercury is a dangerous and toxic metal, thus necessitating an analytical method to ascertain its presence. Traditional methods for mercury analysis often involve costly instruments and specialized expertise. However, the Digital Image Colorimetry (DIC) method is an alternative for mercury detection due to its speed, simplicity, and cost-effectiveness. This research aims to synthesize silver nanoparticles (AgNPs) using Kepundung fruit peel (Baccaurea racemosa) extract as a mercury detector. Baccaurea racemosa has secondary metabolite compounds that can act as natural reducing agents (bioreductors) in synthesizing silver into nanoparticles. AgNPs were optimized and characterized using UV-Vis spectrophotometer, FTIR, PSA, and XRD instruments. Mercury detection was explained using RGB Detector and ImageJ. The research results revealed that the optimal conditions for synthesizing AgNPs involved a concentration of 1% extract and a pH of 7. The properties of the AgNPs included a maximum absorption at wavelengths of 400-450 nm, an average particle size of 122.7 nm, a face-centered cubic crystal structure, and characteristic functional groups at wavenumbers of 3453 cm-1, 1700-1600 cm-1, and 1445 cm-1. These spectral features suggested the presence of phytochemical compounds serving as bioreductants. Optimal results for mercury detection were achieved using Whatman paper no. 41 at pH 7. Mercury was detected successfully, whereas Pb2+, Na+, Mg2+, K+, Cu2+, Ca2+, Co2+, Zn2+, and Fe3+ ions were not detected. The validation test obtained a LoD of 0.099 ppm, a LoQ of 0.330 ppm, and a coefficient value (R2) of 0.997, indicating good measurement linearity. Further research can be developed to increase the sensitivity of mercury detection with lower concentrations and extend its application to environmental samples.